Psychological Well-Being in Obstructive Sleep Apnea Syndrome Associated With Obesity: The Relationship With Personality, Cognitive Functioning, and Subjective and Objective Sleep Quality - Scarpina, Federica; Bastoni, Ilaria; Cappelli, Simone; Priano, Lorenzo; Giacomotti, Emanuela; Castelnuovo, Gianluca; Molinari, Enrico; Tovaglieri, Ilaria Maria Angela; Cornacchia, Mauro; Fanari, Paolo; Mauro, Alessandro (Frontiers in Psychology, 2021)
Obstructive sleep apnea (OSA) syndrome severely affects psychological well-being. This syndrome frequently occurs in obesity; however, no previous study has investigated the level of psychological well-being in the case of OSA syndrome associated with obesity. In this work, we assessed the level of psychological well-being in fifty-two individuals affected by OSA syndrome and obesity through the Psychological General Well-Being Index. Moreover, we investigated the role of personality, cognitive functioning and attentional capabilities, subjective perception and objective measurement about sleeping, on the subjective perception of psychological well-being. Our sample reported a lower level of psychological well-being; the participants’ scores were below the normative cut-off in all components, except for depression symptoms. A lower expression of harm avoidance temperament and a lower level of daily sleepiness predicted a higher level of psychological well-being. Psychological well-being seemed to be severely affected in individuals affected by OSA syndrome and obesity. The temperament characteristics and subjective perception of daily alertness and sleepiness, rather than the syndrome severity, seemed to play a crucial role in the individual perception of the psychological well-being.